Lymphoeosinophilic cholecystitis: A rare cause of acalculous cholecystitis in immunocompetent patients – A case report. (March 2021) - Tran, Steven; Haque, Izhar-ul; Dhatrak, Deepak; Dolan, Paul
Highlights: Lymphoeosinophilic cholecystitis is an important cause of acalculous cholecystitis. Presentations can occur in otherwise well and immunocompetent patients. Cholecystectomy should be offered if the clinical picture fits cholecystitis. Abstract: Introduction: Eosinophilic and lymphoeosinophilic cholecystitis are uncommonly encountered causes of acalculous cholecystitis characterised by a clinical presentation of acute cholecystitis with eosinophilic infiltration of the gallbladder. Acalculous cholecystitis is a disease that is traditionally associated with patients who are critically unwell and immunosuppressed. Presentation of case: A fit and well 37-year-old man presented to the emergency department with a 12 -h history of constant upper abdominal pain radiating through to his back. Abdominal examination revealed tenderness in the right upper quadrant with a positive Murphy's sign. An abdominal ultrasound was performed, revealing a thickened gallbladder wall with probe tenderness, but no gallstones. He proceeded to an uneventful emergency laparoscopic cholecystectomy. Histological examination of the gallbladder revealed mucosal and transmural inflammation comprising of lymphocytes and more than 50 % eosinophils. No gallstones were found. A diagnosis of lymphoeosinophilic cholecystitis was made. The patient had improvement in his symptoms and was discharged home. He was well at follow-up. Discussion: There is a small subset of immunocompetent patients who are not critically unwell who present with acalculous cholecystitis. There is significant hesitancy in offering a cholecystectomy to these patients without radiological evidence of gallstones or sludge preoperatively. Cholecystectomy should be offered to these patients if the clinical picture fits acute cholecystitis. Conclusion: Eosinophilic and lymphoeosinophilic cholecystitis are important causes of acalculous cholecystitis that can occur in immunocompetent patients. The decision to offer the patient a cholecystectomy should be based on clinical presentation and examination, rather than the absence or presence of gallstones.